Learn German, Buy German? Language-learning opportunities abroad and exports - Omar Martin Fieles-Ahmad; Matthias Huber (The World Economy, 2022)
Using data on the presence of the Goethe Institutes (GI) in 134 importer countries between 1978 and 2014, we study the effect that language learning opportunities abroad have on German exports. We employ a gravity model of trade with a single exporter and use the Poisson Pseudo-Maximum Likelihood (PPML) estimator to measure the relationship of interest. To gauge the importance of potential reverse causality, we also estimate the effect that institutes have on Swiss exports. Our findings for both Germany and German-speaking Swiss cantons show that institutes do stimulate exports to GI-hosting countries but that this effect is confined to institutes offering language training services. This finding suggests that language requirements and acquisition underlie the positive link found between institutes and exports. This reading of our findings receives further support in additional explorations, where we study exports differentiated by Rauch (1999, Journal of International Economics, 48(1), 7) product categories to account for differing communication requirements in trading.
Keywords: 330; cultural institute; foreign trade; gravity model; language